Utilization of ICT in Online Education and Training to Enhance Academic Supervision of School Principals - Saefudin, Ady; Sutama, Sutama; Muhibbin, Ahmad; Haryanto, Sigit (Universitas Sebelas Maret, 2024)
The utilization of Information and Communication Technology (ICT) in online education and training for school principals is urgent. This ensures educational leaders have digital skills, enriches teaching methods, and improves managerial efficiency, keeping pace with rapid technological developments. For this reason, this research seeks to dig deeper into aspects of education and training evaluation, especially skills assessment for education and training participants. This qualitative descriptive research sought to describe the actual situation regarding the planning, implementation, and follow-up of skills assessment in the education and training for improving the Academic Supervision Competency of School Principals by utilizing Information and Communication Technology (ICT) at the Institute for the Development and Empowerment of School Principals and School Supervisors (LPPKSPS). The research subjects involved were instructors and principal education and training participants, with a total of six subjects. The results of this research revealed that the skills assessment in education and training developed by LPPKSPS has been designed and implemented in online education and training, and follow-up has been conducted to improve the academic supervision abilities of school principals. Through this research, it is expected that it can become the basis for similar education and training institutions when they want to integrate ICT into education and training activities so that learning outcomes can be achieved optimally.